Improved GFP Variants to Study Gene Expression in Haloarchaea - Born, Johannes; Pfeifer, Felicitas (Frontiers in Microbiology, 2019)
The study of promoter activities in haloarchaea is carried out exclusively using enzymes as reporters. An alternative reporter is the gene encoding the Green Fluorescent Protein (GFP), a simple and fast tool for investigating promoter strengths. However, the GFP variant smRS-GFP, used to analyze protein stabilities in haloarchaea, is not suitable to quantify weak promoter activities, since the fluorescence signal is too low. We enhanced the fluorescence of smRS-GFP 3.3-fold by introducing ten amino acid substitutions, resulting in mGFP6. Using mGFP6 as reporter, we studied six haloarchaeal promoters exhibiting different promoter strengths. The strongest activity was observed with the housekeeping promoters Pfdx of the ferredoxin gene and P2 of the ribosomal 16S rRNA gene. Much lower activities were determined for the promoters of the p-vac region driving the expression of gas vesicle protein (gvp) genes in Halobacterium salinarum PHH1. The basal promoter strength dropped in the order PpA, PpO > PpF, PpD. All promoters showed a growth-dependent activity pattern. The GvpE-induced activities of PpA and PpD were high, but lower compared to the Pfdx or P2 promoter activities. The mGFP6 reporter was also used to investigate the regulatory effects of 5’-untranslated regions (5’-UTRs) of three different gvp mRNAs. A deletion of the 5’-UTR always resulted in an increased expression, implying a negative effect of the 5’-UTRs on translation. Our experiments confirmed mGFP6 as simple, fast and sensitive reporter to study gene expression in haloarchaea.